Protein tyrosine phosphatase PTP1B suppresses p210 bcr-abl-induced transformation of Rat-1 fibroblasts and promotes differentiation of K562 cells - LaMontagne, Kenneth R. (The National Academy of Sciences, 1998)
The bcr-abl chimeric oncoprotein exhibits deregulated protein tyrosine kinase activity and is implicated in the pathogenesis of Philadelphia chromosome (Ph)-positive human leukemias, such as chronic myelogenous leukemia (CML). Recently we have shown that the levels of the protein tyrosine phosphatase PTP1B are enhanced in p210 bcr-abl-expressing cell lines. Furthermore, PTP1B recognizes p210 bcr-abl as a substrate, disrupts the formation of a p210 bcr-abl/Grb2 complex, and inhibits signaling events initiated by this oncoprotein PTK. In this report, we have examined whether PTP1B effects transformation induced by p210 bcr-abl. We demonstrate that expression of either wild-type PTP1B or the substrate-trapping mutant form of the enzyme (PTP1B-D181A) in p210 bcr-abl-transformed Rat-1 fibroblasts diminished the ability of these cells to form colonies in soft agar, to grow in reduced serum, and to form tumors in nude mice. In contrast, TCPTP, the closest relative of PTP1B, did not effect p210 bcr-abl-induced transformation. Furthermore, neither PTP1B nor TCPTP inhibited transformation induced by v-Abl. In addition, overexpression of PTP1B or treatment with CGP57148, a small molecule inhibitor of p210 bcr-abl, induced erythroid differentiation of K562 cells, a CML cell line derived from a patient in blast crisis. These data suggest that PTP1B is a selective, endogenous inhibitor of p210 bcr-abl and is likely to be important in the pathogenesis of CML.